The heterogeneous effects of social cues on day time and night time electricity usage, and appliance purchase: Evidence from a field experiment in Armenia - Yermone Sargsyan; Salim Turdaliev; Silvester Van Koten (Charles University in Prague, Institute of Economic Studies (IES), 2023)
This study investigates the effectiveness of "nudges" through monthly peer comparison reports on household energy consumption in Yerevan, Armenia. We collected data from 300 households for a total of 8 months. While monthly peer comparison reports show no significant effect on energy consumption, we find strong and statistically significant heterogeneous treatment effects. Specifically, we find that households utilizing electricity as their primary heating source, households where the respondent is an educated female, and households with respondents aged 56 and above experienced a decrease in electricity usage as a result of the peer comparison reports. Moreover, we discover that high electricity consumers reduce their consumption significantly after receiving the reports. However, we also observe a small "boomerang" effect, whereby households in the lower quartile of electricity consumption slightly increase their usage in response to the reports. Furthermore, we find that the bulk of the reduction in electricity consumption comes from daytime consumption when the marginal cost of electricity is higher. Additionally, we explore the heterogeneous treatment effects of nudges on the investment in the physical stock of appliances.
Keywords: Q4; Q53; Q48; Q58; C93; 330; demand side management; nudges; household energy consumption; peer comparison; developing country; heterogeneous treatment effects; electrical appliances